Orthodontic management of bilateral maxillary canine impaction in skeletal Class I malocclusion: A case report (Research, Society and Development, 2024)
Introduction: Impacted maxillary canines can assume a diverse array of three-dimensional positions, contributing to the complexity of orthodontic treatment. Objective: This article aims to discuss the case of a skeletal Class I patient with a mesofacial pattern, a convex facial profile and maxillary incisor protrusion, presenting with Class I malocclusion, normal overjet, and a mild overbite, along with bilateral impaction of the permanent maxillary canines. Available treatment options included orthodontic traction of the impacted canines, extraction of the primary canines, either preserving or extracting the impacted canines, or extracting all canines and closing the posterior space. Ankylosis of the right canine was a consideration. The treatment that was implemented involved closed exposition, attachment bonding, and traction of the right canine into the occlusal line using a full fixed appliance. Results: The left canine was extracted, and the primary canine was retained as a placeholder for future prosthetic implantation after growth cessation. After 35 months, the right canine was successfully positioned in the occlusal line, maintaining the left primary canine and the original good intercuspation. Conclusion: The prosthetic rehabilitation with an implant-supported prosthesis on the left side was successful, as confirmed at the 3-year and 4-month follow-up.